The Air War vs. the Ground Game: An Analysis of Multichannel Marketing in U.S. Presidential Elections - Zhang, Lingling; Chung, Doug J. (Marketing Science, 2020)
This study jointly examines the heterogeneous effects of television advertising and field operations in U.S. presidential elections.